Antibiotic 26-deoxylaidlomycin isolated from Streptomyces sp. Ar386 from Brazilian soil - Ujikawa, Keidi [UNESP]; Vilegas, Wagner [UNESP]; Vilegas, Janete H. Y.; Llabrés, Gabriel (My University, 1996)
An actinomycete strain (Ar386) was isolated from the soil of the Araraquara regio, SP, Brazil. The strain, named Streptomyces jacareensis, formed irregular rayed, rugose, grayish-white mycelium with sinuous, branched hyphae carrying rare isolated spores; assimilated glucose, galactose, inositol, ribose, maltose, sucrose, melibiose and starch but not mannitol, rhamnose, arabinose, xylose, lactose and raffinose; and contained LL- diaminopimelic acid in its cell wall. An antibiotic active against Gram- positive bacteria, which was characterized as being 26-deoxylaidlomycin and which may have application against poultry coccidiosis, was isolated from cultures of the strain. This was the first isolation of this antibiotic from a microorganism of the genus Streptomyces and also the first isolation of this antibiotic in Brazil.
Keywords: 26-Deoxylaidlomycin; Coccidiostatic; Polyether antibiotic; Streptomyces jacareensis; Streptomyces sp. Ar386; 26 deoxylaidlomycin; antibiotic agent; arabinose; diaminopimelic acid; galactose; glucose; inositol; lactose; maltose; mannitol; melibiose; raffinose; rhamnose; ribose; starch; sucrose; xylose; antibiotic biosynthesis; antimicrobial activity; bacterial metabolism; bacterium isolation; Brazil; coccidiosis; controlled study; nonhuman; poultry; soil microflora; Streptomyces; streptomyces jacareensis; Monensin; Soil Microbiology